Kaedah peperiksaan bagi murid-murid berkeperluan khas masalah pembelajaran (BKBP) - Mohd. Hanafi Mohd. Yasin,; Mohamed Fauzee Ramli,; Nik Azhar Nik Abd. Rahman,; Md. Amin Kasbin,; Zawawi Zahari, (penerbit ukm, 2010)
This research introduces an alternative method of assessing candidates with learning disabilities without modifying or impacting the quality of the questions. This alternative assessment involves changing the question presentation from a written form to a voice form using computer technology. The sample consists of 163 students from all over Malaysia who have just sat for their Peperiksaan Menengah Rendah (PMR). In this research, three methods of assessment were studied: 1. Regular Method This is the traditional method as being used now. 2. E-Suara I (EsI) is a model where sample read and listen to the questions on the computer and answer by writing in the OMR paper. E-Suara II (EsII) requires sample to read and listen to the questions on the computer and answer questions on the computer. Findings showed that the level of students’achievement as such: Regular Method mean 5.83, EsI mean 8.13 and EsII min 8.35. The findings show that the EsII method enables students with learning disabilities to answer exam questions better than the Regular Method. Through the EsII Method, the ability of students with learning disabilities can be assessed correctly.